A Leadership Development Program for student physical therapists and therapist assistants - Laura LoVasco (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2019)
Leadership in the physical therapy profession has been identifi ed as a characteristic needed for primary care delivery in the healthcare environment [1-5]. The American Physical Therapy Association (APTA) Leadership Development Committee defi ned four core competencies for physical therapists (PTs) and physical therapist assistants (PTAs) who wish to develop their leadership skills [1]. The APTA promotes leadership development in the core competencies by providing recommended on-line resources for developing leadership skills and leadership development opportunities [6]. Two formal leadership programs available within the APTA sections are the Education Leadership Institute (ELI) Fellowship [2] and the Leadership Administration Management Professionalism (LAMP) Leadership Development Certifi cate Program [3].